The Effectiveness of Using Quizizz as an Interactive Medium in Van Hiele Model Geometry Learning to Improve Creative Thinking Skills of Students at MTs Negeri 1 Donggala - Rifka Amanda; Mustamin Idris; Bakri M Bakri M; Fajriani Fajriani (Journal of Educational Sciences, 2026)
This study aims to determine the effectiveness of using Quizizz as an interactive learning medium in Van Hiele model geometry learning on the creative thinking skills of students at MTs Negeri 1 Donggala. This study used a quantitative approach with a quasi-experimental type and a nonequivalent control group pretest-posttest design. The research population was all eighth-grade students at MTs Negeri 1 Donggala, with a sample of 47 students consisting of two classes, selected through random sampling. The instrument used to measure creative thinking skills was a test consisting of two essay questions. The data were analyzed using prerequisite tests (normality and homogeneity tests) and hypothesis testing using an independent-sample t-test with the help of the SPSS program. The results showed that the significance value of the posttest t-test was 0.002 < 0.05, so H0 was rejected and H1 was accepted. The average posttest score of the experimental class was higher than that of the control class. Thus, it can be concluded that the use of Quizizz as an interactive learning medium in Van Hiele model geometry learning is effective in improving the creative thinking skills of students at MTs Negeri 1 Donggala.